2017
DOI: 10.1074/jbc.m117.797001
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of miR-663 controls mitochondria-to-nucleus retrograde signaling and tumor progression

Abstract: The normal cellular function requires communication between mitochondria and the nucleus, termed mitochondria-to-nucleus retrograde signaling. Disruption of this mechanism has been implicated in the development of cancers. Many proteins are known modulators of retrograde signaling, but whether microRNAs (miRNAs) are also involved is unknown. We conducted an miRNA microarray analysis using RNA from a parental cell line, a Rho line lacking mitochondrial DNA (mtDNA) and a Rho line with restored mtDNA. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 80 publications
0
48
0
Order By: Relevance
“…Several miRNAs have been described as directly targeting the OXPHOS subunits or assembly factors ( Figure 6, Table 2B). It was shown that miR-663 positively regulates OXPHOS subunit and assembly factor protein levels by direct stabilization of complex III assembly factor UQCC2 (Carden et al, 2017). In breast cancer cell lines, mitochondrial dysfunction downregulates miR-663 through hypermethylation of its promoter, which leads to decreasing OXPHOS proteins levels and enzymatic activity and stability of supercomplexes, which promotes tumorigenesis (Carden et al, 2017).…”
Section: Oxidative Phosphorylation System (Oxphos)mentioning
confidence: 99%
“…Several miRNAs have been described as directly targeting the OXPHOS subunits or assembly factors ( Figure 6, Table 2B). It was shown that miR-663 positively regulates OXPHOS subunit and assembly factor protein levels by direct stabilization of complex III assembly factor UQCC2 (Carden et al, 2017). In breast cancer cell lines, mitochondrial dysfunction downregulates miR-663 through hypermethylation of its promoter, which leads to decreasing OXPHOS proteins levels and enzymatic activity and stability of supercomplexes, which promotes tumorigenesis (Carden et al, 2017).…”
Section: Oxidative Phosphorylation System (Oxphos)mentioning
confidence: 99%
“…We further characterized miR-663 because this miRNA is potentially associated with immune functions 23 and relevant to SLE disease activity (Figure 1d). MiR-663 has been demonstrated to play a critical role in anti-malignancies [34][35][36] because it induces the differentiation but suppresses the proliferation and invasion of tumor cells. Moreover, miR-663 is important for the key events induced in endothelial cells by stress agents and oxidized lipids, 37 and thus it may have a potential role in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although, an overproduction of free radicals such as superoxide anion (O 2 − ) and hydroxyl radical (OH) can generate unrepaired damage to mtDNA (Han and Chen, 2013), many studies pointed out the regulation of nuclear components through ROS signaling (Larosa and Remacle, 2018). For example, mitochondrial ROS can upregulate the expression of assembly factors of I, II, III, and IV complexes (Carden et al, 2017). In this way, mitochondrial ROS communicate with the nucleus in a bidirectional fashion.…”
Section: Oxidative Stress and Mitochondrial Dysfunction In Alzheimer'mentioning
confidence: 99%